2012
DOI: 10.3109/09286586.2011.628777
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Follow-up after Cataract Surgery in Rural China

Abstract: Modest compensation, advertisements and telephone contact can increase medium-term follow-up rates after cataract surgery by three-fold. Better communication of specific targets for follow-up may improve follow-up compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…[43][44][45][46] This issue is compounded by poor surgical follow-up rates, which can be as low as 20%, making it difficult to assess surgical quality in low-income settings. [47][48][49] Although some developing areas, such as Tanzania and parts of China, have reported rates comparable with developed countries, 27,30 rates are higher in other developing countries (0.033-2.9%). 24,25,28,29,31 Clearly, better surgical training is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46] This issue is compounded by poor surgical follow-up rates, which can be as low as 20%, making it difficult to assess surgical quality in low-income settings. [47][48][49] Although some developing areas, such as Tanzania and parts of China, have reported rates comparable with developed countries, 27,30 rates are higher in other developing countries (0.033-2.9%). 24,25,28,29,31 Clearly, better surgical training is needed.…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost are the less‐than‐optimal surgical outcomes that have been reported from less developed countries . This issue is compounded by poor surgical follow‐up rates, which can be as low as 20%, making it difficult to assess surgical quality in low‐income settings . Although some developing areas, such as Tanzania and parts of China, have reported rates comparable with developed countries, rates are higher in other developing countries (0.033–2.9%) .…”
Section: Discussionmentioning
confidence: 99%
“…One report on early assessment of cataract surgery at 40 hospitals in Africa, Asia and Latin America21 found that the 6-week follow-up rate in China (27%) was the lowest among 11 countries surveyed, while the mean follow-up rate across all institutions was 51%. A report on postcataract surgical follow-up from Africa22 has detailed similar low rates of medium-term follow-up: 54% at 8 weeks postoperatively, though studies in rural China23 24 have demonstrated that phone contact and offers of compensation can result in follow-up at 3–12 months in excess of 80%. The very few studies reporting follow-up rates after glaucoma surgery in developing areas give somewhat higher figures: 84% at 1 month in China14 and 58% at a year in India,9 though neither study was designed specifically to assess follow-up under routine conditions, and these results may not be representative.…”
Section: Discussionmentioning
confidence: 99%
“…The very few studies reporting follow-up rates after glaucoma surgery in developing areas give somewhat higher figures: 84% at 1 month in China14 and 58% at a year in India,9 though neither study was designed specifically to assess follow-up under routine conditions, and these results may not be representative. Among the few studies reporting on determinants of postoperative follow-up after eye surgery in low-income and middle-income countries, lack of knowledge,14 rural residence,14 visual impairment,14 low income23 and failure to recall physician's instructions to return24 were risk factors for poor compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcomes of cataract surgery in low‐resource settings have been variable, with poor long‐term follow‐up, often less than 50% . How then can a low resource setting eye hospital reliably measure the quality of its surgical outcomes?…”
mentioning
confidence: 99%